Combining approaches for early diagnosis of breast diseases using thermal imaging. (1st January 2012) - Borchartt, Tiago B.; Resmini, Roger; Motta, Leonardo S.; Clua, Esteban W.G.; Conci, Aura; Viana, Mariana J.A.; Santos, Ladjane C.; Lima, Rita C.F.; Sanchez, Angel
This paper presents a combination of efforts on the construction of a tool to help in the diagnosis by infrared breast images. It considers from the basic problem of image acquisition and storage in a database to the automatic extraction of the region of interest of each breast (left and right), the feature extraction, the decision and the limits of the diagnosis as well. The main objective of this study is the analysis of the viability of the use of the IR images for automatic detection of pathologies by texture symmetric analysis. Moreover numerical simulations and experimentations are developed in order to analyse the relation between the internal temperature of the breast and the temperature on the breast surface during the image acquisition.